Metronidazole conjugated magnetic nanoparticles loaded with amphotericin B exhibited potent effects against pathogenic Acanthamoeba castellanii belonging to the T4 genotype - Abdelnasir, Sumayah (2020)
Acanthamoeba castellanii can cause granulomatous amoebic encephalitis and Acanthamoeba keratitis. Currently, no single drug has been developed to effectively treat infections caused by Acanthamoeba. Recent studies have shown that drugs conjugated with nanoparticles exhibit potent in vitro antiamoebic activity against pathogenic free-living amoebae. In this study, we have developed a nano drug delivery system based on iron oxide nanoparticles conjugated with metronidazole which were further loaded with amphotericin B to produce enhanced antiamoebic effects against Acanthamoeba castellanii. The results showed that metronidazole-nanoparticles-amphotericin B (Met-MNPs-Amp) significantly inhibited the viability of these amoebae as compared to the respective controls including drugs and nanoparticles alone. Met-MNPs-Amp exhibited IC₅₀ at 50 μg/mL against both A. castellanii trophozoites and cysts. Furthermore, these nanoparticles did not affect the viability of rat and human cells and showed safe hemolytic activity. Hence, the results obtained in this study have potential utility in drug development against infections caused by Acanthamoeba castellanii. A combination of drugs can lead to successful prognosis against these largely neglected infections. Future studies will determine the value of conjugating molecules with diagnostic and therapeutic potential to provide theranostic approaches against these serious infections.